Literature Review of Factors Affecting Occupational Safety Culture - Harahap, Aswin Syapii; Cahaya, Yohanes Ferry (Dinasti International Journal of Management Science, 2025)
Work safety culture has become very important for companies to implement. With a good safety culture, the company will have a lower rate of workplace accidents, higher operational efficiency, and greater trust from employees and stakeholders. Building a strong safety culture is not easy; many challenges and obstacles occur in the field. This study aims to conduct a literature review of previous research on safety culture to identify the factors that influence the development of a good safety culture in companies. The research method used is qualitative research with content analysis techniques on 17 research papers with the keyword "safety culture" downloaded from Google Scholar and ScienceDirect. The research results identified fifteen factors that influence safety culture, namely management commitment, training, rules and procedures, behavior, leadership, beliefs and perceptions, attitudes, worker competence, communication, work environment, values and norms, resource allocation, worker knowledge, rewards and motivation, and worker involvement.